Single Nucleotide Variations in CLCN6 Identified in Patients with Benign Partial Epilepsies in Infancy and/or Febrile Seizures - Yamamoto, Toshiyuki; Shimojima, Keiko; Sangu, Noriko; Komoike, Yuta; Ishii, Atsushi; Abe, Shinpei; Yamashita, Shintaro; Imai, Katsumi; Kubota, Tetsuo; Fukasawa, Tatsuya; Okanishi, Tohru; Enoki, Hideo; et al. (PLOS ONE, 2015)
Nucleotide alterations in the gene encoding proline-rich transmembrane protein 2 (PRRT2) have been identified in most patients with benign partial epilepsies in infancy (BPEI)/benign familial infantile epilepsy (BFIE). However, not all patients harbor these PRRT2 mutations, indicating the involvement of genes other than PRRT2. In this study, we performed whole exome sequencing analysis for a large family affected with PRRT2-unrelated BPEI. We identified a non-synonymous single nucleotide variation (SNV) in the voltage-sensitive chloride channel 6 gene (CLCN6). A cohort study of 48 BPEI patients without PRRT2 mutations revealed a different CLCN6 SNV in a patient, his sibling and his father who had a history of febrile seizures (FS) but not BPEI. Another study of 48 patients with FS identified an additional SNV in CLCN6. Chloride channels (CLCs) are involved in a multitude of physiologic processes and some members of the CLC family have been linked to inherited diseases. However, a phenotypic correlation has not been confirmed for CLCN6. Although we could not detect significant biological effects linked to the identified CLCN6 SNVs, further studies should investigate potential CLCN6 variants that may underlie the genetic susceptibility to convulsive disorders.